Climate Smart Investment Planning by minimizing climate induced price and production risks - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
We have developed this model for Semi-Arid Region in India and Salinity risk-prone region in Bangladesh. The India Model has been published as an IFPRI discussion paper and the Bangladesh model results is under review with the internal experts.